Careers in education for the new woman - Skagen, Kiki. 4 0 16; 5 (New York : Watts, 1977)
Discusses teaching careers on all age levels and in all areas and other careers in the educational field.
Includes index.
Bibliography: p. [107]-109.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Vocational guidance. -- Women teachers.;Teaching;Vocational guidance. -- 20; 20; 2